DEVELOPMENT OF AN AUTOMATED CONTAINERIZED MODEL USING BLOCKCHAIN TECHNOLOGY IN THE EDUCATION SYSTEM - Sabyrkhanova Г.Ш.; Sembiyev О.З.; Esmagambetov Б.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The relevance of the study is determined by the implementation of automated containerized models based on blockchain technologies, which open up new directions for the transformation of the education system. Blockchain technologies contribute to increasing transparency, security, and efficiency in managing educational processes. Currently, digital technologies are rapidly integrating into the education system, transforming traditional teaching and management methods. In this regard, one of the most promising directions is the development and implementation of automated containerized models using blockchain technologies. This approach ensures a high level of transparency, security, and efficiency in the educational environment, while also establishing a foundation for adapting to the challenges of digital transformation. The aim of the study is to conduct a comprehensive analysis and develop the fundamental principles for creating an automated containerized model in the education system using blockchain technologies. To achieve this goal, a specialized educational platform is being developed. The main significance of the platform lies in the creation of an electronic database, the effective use of distance learning technologies, and the implementation of decentralized monitoring to optimize network interaction. The research results have made it possible to define the objectives, tasks, and key principles for developing an information system aimed at automating and optimizing the learning process. This paper examines the advantages of implementing blockchain technologies in higher education and proposes methods for their application to enhance transparency and operational efficiency in educational institutions. The scientific novelty of the study lies in the development of informational tools to support educational activities, improve their efficiency, and integrate traditional methods with new digital technologies. Based on the analysis of the results, the goals and directions for integrating blockchain technologies into the development of the educational platform have been identified. Furthermore, combining blockchain with gamification, big data processing, and artificial intelligence enhances student and teacher motivation, optimizes the learning process, and creates opportunities for personalized development and academic achievement